(3aVGFd CHj HcQ GdUOjb QVi Gddg Yfgs - (3CHh WGdH GdMGaX eMeO Hf Ydj Hf GdaJM Hf GdYTGQj, GHf GdYTGQj,J (B451 (3g` s ((3CMeO Hf CMeO Hf bQGLG GdejOGfi s)
(3ChdgG (B:s
(3CNHQfG GdTjN GdEeGe GdMGaX GdVGHW GdeJbf HbjI GdSda hYeOI GdNda CHhGdMSf Ydi Hf EHQGgje Hf OGhO Hf GdYWGQ GdOeTbi GdTGaYi SeGYkG s
(3YdjgG SeGYGJ cKjQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B276s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B601 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B198 s
Keywords: (3GdJGQjNs